2007
DOI: 10.1007/s10461-007-9241-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Mediates the Relationship between Adherence Self-efficacy and Biological Assessments of HIV Health among those with Alcohol Use Disorders

Abstract: The current study examines the relationship between negative consequences of alcohol use, adherence self-efficacy, medication adherence, and biological markers of HIV health (CD4 count and viral load). A total of 275 HIV-positive men and women with alcohol use disorders were surveyed using Audio-CASI measures and time line followback interviews. Findings from a structural equation model suggest that negative consequences related to alcohol use did not directly impact HIV health. Adherence self-efficacy had dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
3
28
0
3
Order By: Relevance
“…Esse mesmo autor encontrou associação significativa em dois outros artigos publicados em 2007. Em um desses artigos, escrito juntamente com Rosof e Mustanski, Parsons avaliou os subfatores do padrão de uso de álcool e demonstrou que entre os não aderentes é a quantidade de drinks consumidos pelo indivíduo que prediz se haverá ou não falhas na adesão [17][18][19][20][21] .…”
Section: Resultsunclassified
“…Esse mesmo autor encontrou associação significativa em dois outros artigos publicados em 2007. Em um desses artigos, escrito juntamente com Rosof e Mustanski, Parsons avaliou os subfatores do padrão de uso de álcool e demonstrou que entre os não aderentes é a quantidade de drinks consumidos pelo indivíduo que prediz se haverá ou não falhas na adesão [17][18][19][20][21] .…”
Section: Resultsunclassified
“…They might have endured poor self-efficacy and not sought appropriate care for opportunistic infections and physical symptoms [39]. Alcohol further increases the risk of the HIV disease progression such as leading to a decrease in CD4 count and an increase in viral load [40].…”
Section: Discussionmentioning
confidence: 99%
“…18 In a variety of therapeutic classes, inconsistent adherence is associated with poor clinical outcomes, treatment failure, and increased health care costs. [19][20][21][22][23] In general, patients utilizing specialty community pharmacies receive more personalized care and have better adherence rates compared with those in nonspecialty community pharmacies. 15,[24][25][26][27] A pilot study found that Medi-Cal beneficiaries with HIV who received medication therapy management (MTM) in community pharmacies that specialized in providing HIV-intensive MTM services had higher adherence rates that persisted over 3 years, compared with patients in pharmacies not providing these services.…”
Section: Opinions Of a Small Sample Of Pharmacists About Pharmacymentioning
confidence: 99%